The Relationship of Neuropsychological Variables to Driving Status Following Holistic Neurorehabilitation - Perumparaichallai, Ramaswamy Kavitha; Husk, Kristi L.; Myles, Stephen M.; Klonoff, Pamela S. (Frontiers in Neurology, 2014)
Objective: The main objectives of the present study were to evaluate the cognitive and driving outcomes of a holistic neurorehabilitation program and to examine the relationship between the neuropsychological variables of attention, speed of information processing, and visuospatial functioning and driving outcomes. Methods: One hundred and twenty eight individuals with heterogeneous neurological etiologies who participated in a holistic neurorehabilitation program. Holistic neurorehabilitation consisted of therapies focusing on physical, cognitive, language, emotional, and interpersonal functioning, including training in compensatory strategies. Neuropsychological testing was administered at admission and prior to starting driving or program discharge. Subtests of processing speed, working memory, and perceptual reasoning from the Wechsler Adult Intelligence Scale-III and Trail Making Test were included. Results: At the time of discharge, 54% of the individuals returned to driving. Statistical analyses revealed that at the time of discharge: the sample as a group made significant improvements on cognitive measures included in the study; the driving and non-driving groups differed significantly on aspects of processing speed, attention, abstract reasoning, working memory, and visuospatial functions. Further, at the time of admission, the driving group performed significantly better than the non-driving group on several neuropsychological measures. Conclusions: Cognitive functions of attention, working memory, visual-motor coordination, motor and mental speed, and visual scanning significantly contribute to predicting driving status of individuals after neurorehabilitation. Holistic neurorehabilitation facilitates recovery and helps individuals gain functional independence after brain injury.